Effect of Politics on Women’S Quota: a Study Upon Women’S Reservation: Examining the Impact of Politics on Women's Quota: A Comparative Study on Gender Representation in Governments (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Itis surely noteworthy that the last decades so often referred to as the era ofglobalisation, have also witnessed a new interest in the politics of governanceworldwide. Interestingly, governance discourse has displayed a particularconcern with questions of gender equality, especially in the sphere ofpolitical representation. Countries as diverse as the United States, France,India and Japan have thus been subjected to the glare of negative attention, inthe face of the low proportion of seats occupied by women within theirrespective governments.